A Detailed Set of Ideas for Designing a Quantum Computing Framework Based on Smart Contracts, Configured Using Foundry and Qiskit - Alexandru-Gabriel Tudorache (Emitter: International Journal of Engineering Technology, 2025)
The purpose of this paper is to describe a new system design for integrating quantum computing algorithms (and their results) into a blockchain network. In this selected context, we can use, create and upload smart contracts (SCs) that allow users to perform various quantum computations, by using the corresponding circuits. We are therefore proposing a system that uses gas fees in the blockchain context, in order to offer access to certain circuits and their simulation results; the system also allows for the previously analyzed circuits to become publicly available, through SCs – this can act like a quantum circuit encyclopedia. Most users in the first generation will have to pay, in addition to the normal transaction fees (gas) required to call the SC methods, a small development fee for the contract creation for most of the tasks; after a certain number of SCs, enough configurations and results will become accessible to everyone, and only custom, unprocessed circuits will require the development fee. Optionally, a dedicated blockchain network (similar to one of the existing test ones) can also be designed, with contracts that have access to real quantum hardware; its owners can decide (if necessary) the value of the virtual coin in connection to a real-world currency. For our experiments, we selected the Solidity language for the development of SCs, and Python for the development and simulation of quantum circuits, with the help of the Qiskit framework, an open-source library for quantum processing developed by IBM.